Enhanced Graphene Plasmonic Mode Energy for Highly Sensitive Molecular Fingerprint Retrieval. Issue 1 (22nd November 2020) - Nong, Jinpeng; Tang, Linlong; Lan, Guilian; Luo, Peng; Li, Zhancheng; Huang, Deping; Yi, Juemin; Shi, Haofei; Wei, Wei
Abstract: Graphene plasmons with tightly confined fields and actively tunable resonant frequencies enable the selective detection of molecular vibrational fingerprints with ultrahigh sensitivity, significantly promoting the development of surface‐enhanced infrared absorption spectroscopies (SEIRAS). However, current experimentally obtained enhancements are much smaller than the theoretical prediction due to the extremely low graphene plasmonic mode energy. In this paper, the strategies to improve the mode energy are theoretically and experimentally investigated in a one‐port graphene plasmonic system. By optimizing the Fabry–Pérot cavity length and employing multi‐layer graphene to drive the system into the near critical coupling regime, the localized graphene plasmonic absorptions can be improved from 3% to more than 92%. This induces a 37 times improvement of graphene plasmonic mode energy from 0.4 × 10 −13 to 1.5 × 10 −12 J per period for the strong plasmon–molecule interactions, enabling the highly sensitive detection of 8 nm thick molecular film. The SEIRAS experimental results demonstrate that a maximum enhancement factor of 162 can be achieved, which is one order larger than that of the reported localized graphene plasmonic sensors. The results showcase the practical usability of localized graphene plasmons for the next‐generation high sensitive nanoscale infrared spectroscopy. Abstract : The localized graphene plasmonic absorption is improved from 3% to 92% combining a Fabry–Pérot like cavity and multi‐layer graphene nanostructures. Such high plasmonic response significantly improves the graphene plasmonic mode energy, which enables the ultrasensitive detection of molecular vibrational fingerprints. The enhancement factor is one order higher than that of the previous reported localized graphene plasmons based sensors.